Rancang Bangun Sistem Pakar Berbasis Web untuk Diagnosis Kerusakan Smartphone Menggunakan Metode Forward Chaining - Atika Fauziyyah; Dori Gusti Alex Candra; Eka Sofiati; Budi Permana Putra; M. Agung Vafky Ideal; Asep Supriyanto (Riau Jurnal Teknik Informatika, 2026)
The rapid advancement of information technology has made smartphones essential devices for supporting various daily activities. Intensive smartphone usage may lead to hardware and software failures, while users' limited knowledge in identifying these failures often results in improper troubleshooting. This study aims to design and develop a web-based expert system for diagnosing smartphone failures using the Forward Chaining method. The system was developed through requirements analysis, expert knowledge acquisition, knowledge base design, rule base construction, method implementation, and system testing. The knowledge base consists of 15 symptoms, 10 types of smartphone failures, and 20 diagnostic rules. The results of Black Box Testing showed that all system functions operated according to the specified requirements with a 100% success rate. Furthermore, validation using 20 test cases demonstrated that 19 system diagnoses were consistent with expert diagnoses, resulting in an accuracy of 95%. The developed expert system can assist users and technicians in performing initial smartphone failure diagnosis quickly, accurately, and efficiently.